Shocks in the Outflow of the RS Oph 2021 Eruption Observed with X-Ray Gratings - Orio, Marina (2022)
The 2021 outburst of the symbiotic recurrent nova RS Oph was observed with the Chandra High Energy Transmission Gratings (HETG) on day 18 after optical maximum and with XMM-Newton and its Reflection Grating Spectrographs (RGS) on day 21, before the supersoft X-ray source emerged and when the emission was due to shocked ejecta. The absorbed flux in the HETG 1.3-31 Å range was 2.6 × 10-10 erg cm-2 s-1, three orders of magnitude lower than the γ-ray flux measured on the same date. The spectra are well fitted with two components of thermal plasma in collisional ionization equilibrium, one at a temperature ≃ 0.75 keV and the other at a temperature in the 2.5-3.4 keV range. With the RGS we measured an average flux of 1.53 × 10-10 erg cm-2 s-1 in the 5-35 Å range, but the flux in the continuum and especially in the lines in the 23-35 Å range decreased during the 50 ks RGS exposure by almost 10%, indicating short-term variability on a timescale of hours. The RGS spectrum can be fitted with three thermal components, respectively at plasma temperatures between 70 and 150 eV, 0.64 keV, and 2.4 keV. The post-maximum epochs of the exposures fall between those of two grating spectra observed in the 2006 eruption on days 14 and 26: they are consistent with a similar spectral evolution, but in 2021 cooling seems to have been more rapid. Iron is depleted in the ejecta with respect to solar values, while nitrogen is enhanced.